The association between body mass index, exercise capacity, and health-related quality of life in heart transplant recipients - Holt, Margrethe Flesvig; Holmen, Stine; Rolid, Katrine; Englund, Kristine V. Brautaset; Østby, Charlotte M.; Ravnestad, Håvard; Andreassen, Arne K.; Gullestad, Lars; Gude, Einar; Broch, Kaspar (Frontiers in Transplantation, 2024)
Introduction: Pre-transplant obesity and weight gain after heart transplantation are both associated with increased risk of poor clinical outcomes. We aimed to assess the association between overweight or obesity, exercise capacity, and health-related quality of life in heart transplant recipients. Methods: This study is based on baseline data from the IronIC trial, in which we randomized 102 heart transplant recipients with iron deficiency to ferric derisomaltose or placebo. We performed cardio pulmonary exercise testing in all participants. To assess quality of life, we used the SF-36v2 questionnaire, using two sum scores: the physical component summary and the mental component summary. A minimal clinically important difference was defined as ≥ 2 and ≥ 3 for the physical and the mental component summary, respectively. Results: 24/102 heart transplant recipients (24 %) had a body mass index (BMI) ≥ 30 kg/m2. Peak oxygen consumption was 17.3 ± 4.6 ml/kg/min in the obese group vs. 24.7 ± 6.4 ml/kg/min in the group with a BMI < 30 for a between-group difference of 7.4 (95 % confidence interval 4.7 – 10.2) ml/kg/min: p < 0.001. The physical component summary score was on average 5.2 points lower in the patients with a body mass index ≥ 30 than in the lower weight group (p = 0.04). Conclusion: Almost a quarter of our heart transplant recipients in long-term follow-up had a BMI ≥ 30 kg/m2. These patients had substantially lower exercise capacity and lower quality of life in the physical domain.